Navigating the way to onchocerciasis elimination: the feasibility and affordability of Onchocerciasis Elimination Mapping. (16th February 2022) - Hamill, Louise; Trotignon, Guillaume; MacKenzie, Charles; Hill, Becks; Pavluck, Alex; Yumba, Dyesse; Isiyaku, Sunday; William, Adamani; Nyior, Audrey; Igbe, Michael; Anyaike, Chukwuma; Akilah, Joel; et al.
Abstract: Background: Onchocerciasis is targeted for elimination of transmission by 2030 in at least 21 countries. To achieve this, recent and accurate data on the extent and intensity of onchocerciasis transmission are required. This will include mapping areas previously unassessed, or remapping of areas that were last visited as part surveys aiming to prevent blindness, not assess transmission in totality. There is near universal acceptance of the need to carry out these mapping reassessments, to achieve equitable and lasting elimination of onchocerciasis transmission. However, there is no consensus on how to conduct onchocerciasis elimination mapping (OEM), and little published data to inform policymakers and programme managers, including on cost. Methods: Here, we summarise the methods and cost implications of conducting pilot OEM surveys in Ghana and Nigeria in 2018. We have included a breakdown of costs incurred overall, per person and per implementation unit in each country, as well as detailed analysis of the cost categories and the main cost drivers. Results: The procurement and logistics of diagnostics accounted for more than one-third of the total cost, a significant cost driver. Conclusions: This information will be valuable to policymakers and donors as they seek to prioritise onchocerciasis elimination and plan to complete OEM.